2013
DOI: 10.1371/journal.ppat.1003223
|View full text |Cite
|
Sign up to set email alerts
|

Glycomic Analysis of Human Respiratory Tract Tissues and Correlation with Influenza Virus Infection

Abstract: The first step in influenza infection of the human respiratory tract is binding of the virus to sialic (Sia) acid terminated receptors. The binding of different strains of virus for the receptor is determined by the α linkage of the sialic acid to galactose and the adjacent glycan structure. In this study the N- and O-glycan composition of the human lung, bronchus and nasopharynx was characterized by mass spectrometry. Analysis showed that there was a wide spectrum of both Sia α2-3 and α2-6 glycans in the lung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
252
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 222 publications
(265 citation statements)
references
References 36 publications
9
252
4
Order By: Relevance
“…2 Table 2). The pattern of binding to the major analogs of human receptors 6=SL, 6=SLN, and sulfated 6-Su-6=SLN and the surrogate of human receptors Neu5AcBn (30) was identical among all viruses tested ( Table 2 shows Table 2). Interestingly, the mutations at amino acids that we identified as determinants of the antigenic phenotype contributed to the switch in binding affinity.…”
Section: Resultsmentioning
confidence: 92%
“…2 Table 2). The pattern of binding to the major analogs of human receptors 6=SL, 6=SLN, and sulfated 6-Su-6=SLN and the surrogate of human receptors Neu5AcBn (30) was identical among all viruses tested ( Table 2 shows Table 2). Interestingly, the mutations at amino acids that we identified as determinants of the antigenic phenotype contributed to the switch in binding affinity.…”
Section: Resultsmentioning
confidence: 92%
“…It was previously reported that a wide range of sialylated O-and N-glycans are extensively expressed on the human airway tract (28). Therefore, it might be possible that our method using trisaccharides failed to detect the differences in binding patterns which are present only in the naturally existing glycans in the human airway tract.…”
Section: Discussionmentioning
confidence: 92%
“…Interestingly, a previous study showed that an overlay of human mucus on MDCK cell monolayers seemed to be more inhibitory to viruses than an overlay of porcine mucus, despite similar sialic acid content, although this effect showed some strain specificity (20). The porcine and human respiratory glycomes show similarities, including the expression of ␣2,3 and ␣2,6 sialylated glycoproteins and large complex N-glycans with sialylated poly-LacNAc chains, but differences have been characterized (34,35). One difference is that humans express N-acetylneuraminic acid (Neu5Ac) and lack N-glycolylneuraminic acid (Neu5Gc), which is expressed in pigs (36,37).…”
Section: Discussionmentioning
confidence: 99%